Polyesters Based on Linoleic Acid for Biolubricant Basestocks: Low-Temperature, Tribological and Rheological Properties - Abdullah, Bashar Mudhaffar; Zubairi, Saiful Irwan; Huri, Hasniza Zaman; Hairunisa, Nany; Yousif, Emad; Basu, Roma Choudhury (Public Library of Science, 2016)
Presently, plant oils which contain high percentage of linoleic acid 1 are perceived to be a viable alternative to mineral oil for biolubricant applications due to their biodegradability and technical properties. In order to get biodegradable lubricant, triester derivatives compounds (1-5) were synthesized and characterized. The processes involved were monoepoxidation of linoleic acid 2, oxirane ring opening 3, esterification 4 and acylation 5. The structures of the products were confirmed by FTIR, 1H and 13C-NMR and LC-MS. The results that showed lowest temperature properties were obtained for triester 5, with a pour point value (PP) of -73°C, highest onset temperature (260°C) and lowest volatility at 0.30%. Viscosity index (VI) increased for the ester's synthetic compounds (2, 3, 4, 5), while the PP decreased. This behavior is the result of the increase of the chain length of the branching agents. Triester based linoleic acid has improved properties such as low-temperature and tribological properties. These results will make it feasible for plant oil to be used for biolubricants, fuels in chain saws, transmission oil and brake fluid.